Translating extracellular vesicle packaging into therapeutic applications - Ozkocak, Dilara C.; Phan, Thanh Kha; Poon, Ivan K. H. (Frontiers in Immunology, 2022)
Extracellular vesicles (EVs) are membrane-bound particles released by cells in various (patho)physiological conditions. EVs can transfer effector molecules and elicit potent responses in recipient cells, making them attractive therapeutic agents and drug delivery platforms. In contrast to their tremendous potential, only a few EV-based therapies and drug delivery have been approved for clinical use, which is largely attributed to limited therapeutic loading technologies and efficiency. As EV cargo has major influence on their functionality, understanding and translating the biology underlying the packaging and transferring of biomolecule cargos (e.g. miRNAs, pathogen antigens, small molecule drugs) into EVs is key in harnessing their therapeutic potential. In this review, through recent insights into EVs’ content packaging, we discuss different mechanisms utilised by EVs during cargo packaging, and how one might therapeutically exploit this process. Apart from the well-characterised EVs like exosomes and microvesicles, we also cover the less-studied and other EV subtypes like apoptotic bodies, large oncosomes, bacterial outer membrane vesicles, and migrasomes to highlight therapeutically-diverse opportunities of EV armoury.